Deconstructing Shinto - Johnson, Stephen M. (Tufts Archival Research Center, 2015)
While the majority of people understand Shinto to be Japan's "indigenous, polytheistic, ancient, religion" in this paper I set out to systematically demonstrate why each of these labels is problematic and misleading. The greater part of my research involved the construction of a genealogy of the terms "religion" and "Shinto" in Japan to demonstrate that this interpretation is a constructed myth of the recent past. My hope is that this paper/its future expansion will help to problematize all such seemingly coherent understandings of Shinto as this one